2021
DOI: 10.3892/wasj.2021.118
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic perspectives ofp‑coumaric acid: Anti‑necrotic, anti‑cholestatic and anti‑amoebic activities

Abstract: Phenolic acids are phytochemical compounds derived from plant biomass materials, that have notable health benefits with high therapeutic potential in several diseases. p-coumaric acid (p-CA) is a phenolic acid that displays various biological activities, such as antioxidant, anti-inflammatory, analgesic and anti-antimicrobial properties. However, the ability of p-CA to prevent hepatic necrosis and cholestasis induced by various harmful agents has not yet been explored to date, at least to the best of our knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…BPAs also included 3.5-dihydroxybenzoic, m-coumaric, and caffeic acid ( Table 2 ). All the PAs found in Camelina seeds and sprouts have beneficial effects on human health, they act as antioxidants and anti-inflammatory, antimicrobial, antitumor, antiviral, antifungal, antidiabetic, and hepatoprotective agents [ 47 , 48 , 49 ]. The germination improved the health properties of Camelina sativa by increasing the content and the number of types of PAs.…”
Section: Resultsmentioning
confidence: 99%
“…BPAs also included 3.5-dihydroxybenzoic, m-coumaric, and caffeic acid ( Table 2 ). All the PAs found in Camelina seeds and sprouts have beneficial effects on human health, they act as antioxidants and anti-inflammatory, antimicrobial, antitumor, antiviral, antifungal, antidiabetic, and hepatoprotective agents [ 47 , 48 , 49 ]. The germination improved the health properties of Camelina sativa by increasing the content and the number of types of PAs.…”
Section: Resultsmentioning
confidence: 99%
“…This compound can be converted into other phenolic acids such as sinapic acid, caffeic acid, and ferulic acid, also other metabolite acids such as lignins and lignin precursors. The studies have shown that para-coumaric acid has several biological activities such as anti-inflammatory, anti-oxidant, anti-platelet aggregation, analgesic, anti-cancer and neuroprotective 44 , 45 . According to our results, since P. glabrum had the ability to produce para-coumaric acid, it could be considered as a suitable source for the production of this compound on a commercial scale.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that p-CA possesses multiple bioactivities of pharmacological qualities that support its ability to have impacts on blood sugar, hyperlipidaemia, neurodegeneration, analgesia, arthritis, anxiolysis, cancer, ulcers, oxidation, anti-platelet aggregation and inflammation [36][37][38] . Coumaric acid have also been report to prevent liver damage induced by CCl 4 or BDL (necrosis and cholestasis) and exhibits amoebostatic activity against Entamoeba histolytica 39 .…”
Section: Discussionmentioning
confidence: 99%